SYNTHESIS, ANTIMICROBIAL ACTIVITY AND MOLECULAR DOCKING STUDY OF SOME NEW N-BENZYL AND N-BENZOYL-3-INDOLYL HETEROCYCLES - Abo-salem, Heba M.; Abdel-aziem, Anhar; Islam, Inas E.; Yossef, Mariam M.; El-sawy, Eslam R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Chalcones are one of the major classes of the natural products, which display a wide range of pharmacological properties. Also, chalcones are well-known intermediates for synthesizing various heterocyclic compounds like pyrazoline and pyrimidine derivatives. The present work is designed to synthesize new 3-indolylheterocycles starting from N-benzyl and N-benzoyl-1H-indole-3-carboxaldehyds and evaluating theirs in vitro antimicrobial activity. In addition, the probability of the most promising antimicrobial compounds to inhibit ATPase, enoyl reductase and dihydrofolate reductase were studied theoretically via molecular docking. Methods: A new series of 3-indolylchalcones 2a,b were prepared and allowed to react with hydrazine hydrate, phenyl hydrazine, hydroxylamine, urea, thiourea and guanidine to afford the corresponding pyrazoles 3a,b-6a,b and pyrimidines derivatives 7a,b-9a,b. On the other hand, the reaction of 2a, b with malononitrile afforded 10a, b, which upon cyclo-condensation with formic acid, formamide, urea or thiourea yielded the fused pyrido [2,3-d]pyrimidine 11a,b-14a,b. Moreover, cyclo-condensation of 2a, b with thiosemicarbazide gave pyrazolin-1-carbothioamides 15a, b, which under cyclization with phenacyl bromide afforded thiazole derivatives 16a and 16b. While the reaction of 2a, b with cyano thioacetamide afforded 2-mercaptonicotinonitriles 17a, b. The reaction of 17a, b with some halo-compounds gave S-alkyl derivatives 18a-d and 19a-d, respectively,which under heating in the presence of piperidine gave the fused thienopyridines 20a-d and 21a-d, respectively. All the newly prepared compounds were evaluated for their in vitro antimicrobial activity. In addition, molecular docking study of the most promising antimicrobial compounds against ATPase, enoyl reductase and dihydrofolate reductase theoretically is discussed. Results: Compounds 17a and 17b were found to be the most potent compounds with MIC of 0.98, 0.49 and 0.98Âµg/ml against S. pneumoniae (RCMB 010010), E. coli (RCMB 010052) and A. fumigatus (RCMB 02568), respectively compare to the reference drugs. Also, compounds 17a and 17b exhibited good docking scores and could act as inhibitors of enzymes understudied. Conclusion: Further work is recommended to confirm the ability of compounds 17a and 17b to inhibit ATPase, enoyl reductase and dihydrofolate reductase in a specific bioassay.